Capabilities, Well-Being and Multiculturalism: A New Framework for Guiding Policy - Hodgett, Susan; Clark, David (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2011)
This paper develops an Integrated Capabilities Framework for investigating human well-being in multicultural settings, shows how it can be made operational through fieldwork and argues it has practical and policy relevance for studying immigration, multiculturalism, and social cohesion in Canada.